Increasing the sensitivity of 2D high-resolution NMR methods applied to quadrupolar nuclei - Amoureux, J. P.; Delevoye, L.; Steuernagel, S.; Gan, Zhengting; Ganapathy, Subramanian; Montagne, L. (Journal of Magnetic Resonance, 2005)
Gan and Kwak recently proposed a soft-pulse added mixing (SPAM) idea in the classical two-pulse multiple-quantum magic-angle spinning scheme. In the SPAM method, a soft pi/2 pulse is added after the second hard-pulse (conversion pulse) and all coherence orders in between them are constructively used to obtain the signal. We, here, further extend this idea to distributed samples where the signal mainly results from echo pathways and that from anti-echo pathways dies Out after a few t(1) increments. We show that, with a combination of SPAM and collection of fewer anti-echoes, an enhancement of the signal to noise ratio by a factor of ca. 3 may be obtained over the z-filtered version. This may prove to be useful even for samples with long T'(2) relaxation times. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: high-resolution; quadrupolar nuclei; sensitivity; Solid-state NMR

Effect of spacer groups on the performance of MCM-41-supported platinum cluster-derived hydrogenation catalysts - Maity, Niladri; Basu, Susmit; Mapa, Maitri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
MCM-41 was functionalized with (EtO)(3)SiCH2Cl, (MeO)(3)SiCH2CH2CH2Cl, and (CH3)Cl2SiCH2Cl. The functionalized materials were characterized by solid-state NMR (CPMAS, Si-29 and C-13) and XPS. The NMR data indicate that three new silicon environments were created by(EtO)(3)SiCH2Cl and (MeO)(3)SiCH2CH2CH2Cl, whereas with (CH3)Cl2SiCH2Cl, two new silicon environments were obtained. XPS results from Si 2p core level and the valence band from the material functionalized by (MeO)(3)Si(CH2)(3)Cl was found to be the same as that of the corresponding fresh catalyst (1a), in contrast to that of the materials functionalized by the other two silane reagents. After further functionalization with triethylamine, these materials were used as inorganic anion exchangers to support the cluster anion [Pt-12(CO)(24)](2-). Solid-state NMR (29Si, C-13, N-15) was used to establish the presence of the quaternary ammonium group in the cluster-supported species. Analogous materials were also created using fumed silica as the support, and all of the cluster-supported materials were tested as catalysts for the hydrogenation of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, ethylacetoacetate, 4-nitrotoluene, cyclohexanone, allyl alcohol, and styrene. The best activity was obtained for the catalyst that had MCM-41 as the support and chloropropyl as the spacer group. TEM showed that the supports and the spacer groups had observable effects on the platinum crystallite size of the catalysts. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: functionalized inorganic oxides; hydrogenation catalysts; MCM-41; platinum carbonyl cluster; Solid-state NMR; spacer groups; XPS

Heteronuclear dipolar decoupling effects on multiple-quantum and satellite-transition magic-angle spinning NMR spectra - Ganapathy, Subramanian; Delevoye, L.; Arnoureux, J. P.; Madhu, Perunthiruthy K. (Magnetic Resonance in Chemistry, 2008)
We here report on the influence of heteronuclear dipolar decoupling on the Al-27 3QMAS, 5QMAS, and the double-quantum filter-satellite-transition magic-angle spinning (DQF-STMAS) spectra of a strongly dipolar-coupled system, gibbsite. The requirements for heteronuclear dipolar decoupling increase with the order of coherence evolving in the indirect dimension of a two-dimensional (2D) experiment. The isotropic line width of the high-resolution 2D spectra, in samples like gibbsite, is composed of four parts: the distribution of isotropic shifts (delta(ISO), delta(QIS)), the homogeneous broadening related to the proton-proton flip-flop terms, the Al-27-Al-27 homonulcear dipolar couplings, and the H-1-Al-27 heteronuclear dipolar couplings. It is shown that, even in the case of gibbsite, where a strong proton-proton bath exists, the main resolution limiting factor in these experiments resides in the H-1-Al-27 dipolar interaction. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: heteronuclear broadening; heteronuclear decoupling; homogeneous broadening; MQMAS; quadrupolar nuclei; Solid-state NMR; STMAS; TPPM

MCM-41-supported organometallic-derived nanopalladium as a selective hydrogenation catalyst - Maity, Niladri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Physical Chemistry C, 2008)
Palladium nanocatalysts have been prepared by anchoring (eta(3)-C(3)H(5))(2)Pd(2)Cl(2) onto dian-tine-functionalized MCM-41 supports followed by reaction with hydrogen under catalytic conditions. The catalyst precursor and used catalyst have been studied by solid-state NMR ((13)C, (29)Si), XPS, and TEM. The organometallic-derived catalyst exhibits the best performance (activity and selectivity) to date toward the selective hydrogenation of industrially relevant o- and m-chloronitrobenzene to the corresponding chloroaniline derivatives and is distinctly superior to 5% Pd/C. Grazing angle XPS studies reveal that conversion of the tethered molecular species to the nanoparticles of palladium produces a core-shell nanostructure.

Sn-119 magic angle spinning NMR of nanocrystalline SnO2 - Sabarinathan, V.; Chandran, C. Vinod; Ramasamy, S.; Ganapathy, Subramanian (Journal of Nanoscience and Nanotechnology, 2008)
Nanocrystalline SnO2 samples of different grain sizes, prepared by inert gas condensation technique (IGCT) and chemical precipitation method and conforming to the tetragonal phase, have been studied by variable speed (3-10 kHz) Sn-119 MAS NMR at 11.74 Tesla field. Sn-119 solid-state NMR results show that the IGCT prepared samples have good crystallinity and phase purity compared to the samples prepared by the chemical method. The determination of Sn-119 chemical shielding parameters (delta(iso), Delta delta and eta) from slow MAS spectra shows that the Sn-119 isotropic chemical shift (delta(iso)) is strongly influenced at smaller grain sizes, attributable to the change in the O2- local symmetry for the surface Sn-119 ions at smaller grain sizes. The observed line widths in MAS spectra are significantly larger than the life-time broadening due to spin-lattice (T-1) and spin-spin (T,) relaxation. The Sn-119 MAS NMR spectra are thus inhomogeneously broadened by a distribution of isotropic chemical shifts, the line broadening increasing with decrease in grain size.
Keywords: Hydrolysis; IGCT; MAS NMR; nanocrystalline SnO2

Sensitivity enhancement of Si-29 double-quantum dipolar recoupling spectroscopy by Carr-Purcell-Meiboom-Gill acquisition method - Goswami, M.; Madhu, Perunthiruthy K.; Dittmer, J.; Nielsen, N. C.; Ganapathy, Subramanian (Chemical Physics Letters, 2009)
An enhancement in the detection sensitivity of dipolar recoupled Si-29 double-quantum magic-angle spinning experiment is shown with a Carr-Purcell-Meiboom-Gill (CPMG) train of pi pulses during the acquisition period. Symmetry-adapted pulse schemes, such as POST-C7 and SR26(4)(11), are used for the double-quantum excitation. Application of POST-C7-CPMG method for framework characterisation is demonstrated in the disordered and catalytically important ZSM-5 molecular sieve. Based on the observed double-quantum dipole-dipole correlations and the known T-site Si connectivities, the assignment of all the signals is made for the orthorhombic phase of the as-synthesised (CN form) material. (C) 2009 Elsevier B. V. All rights reserved.

Perturbations to Al-27 electric field gradients in nanocrystalline alpha-Al2O3 studied by high-resolution solid-state NMR - Sabarinathan, V.; Ramasamy, S.; Ganapathy, Subramanian (Journal of Physical Chemistry B, 2010)
Al-27 solid-state NMR has been employed to study the perturbations to Al-27 electric field gradients for the aluminum environments in nanocrystalline alpha-alumina. Triple quantum magic angle spinning experiments show that the octahedral aluminum coordination remains unchanged down to 12 nm, although severe perturbations to Al-27 electric field gradients are noticed at 28 nm and below. 3Q-MAS and SATRAS experimental data of nano alpha-alumina have been analyzed through extensive spectral simulations to probe Al-27 electric field gradients of aluminum in the grains and grain boundaries. While the aluminum in the grains has a unique field gradient tensor, the same octahedrally coordinated aluminum environments in the grain boundaries suffer a distribution of electric field gradients. This is evidenced by data analysis of both 3Q-MAS and SATRAS spectra. By invoking the Gaussian isotropic model, in which the (C-Q, eta(Q)) parameter space is discretely sampled by the Czjzek distribution, we have been able to analyze the Al-27 SATRAS spectra of nanocrystalline alpha-alumina samples having grain sizes of 52, 28, 20, and 12 nm. Good agreement between experimental and simulated spectra has led to the quantitative determination of grain and grain boundary components in these materials.

Identification of sublattice damages in swift heavy ion irradiated N-doped 6H-SiC polytype studied by solid state NMR - Viswanathan, E.; Kanjilal, D.; Sivaji, K.; Ganapathy, Subramanian (Journal of Physical Chemistry B, 2011)
We have studied N-doped 6H-SiC in its pristine and Swift Heavy Ion (SHI) irradiated (150 MeV Ag12+ ions) forms by solid state Nuclear Magnetic Resonance (NMR) at 7.01 T using C-13 and Si-29 as probe nuclei under magic angle spinning. We show that increased levels of nitrogen doping, than used before, lead to the observation of Knight shifts emanating from an increase in electron density in the conduction band, which in C-13 far exceed those in Si-29 MAS spectra. We have rationalized the differential effects in the MAS spectra and site-dependent paramagnetic shifts in terms of the nitrogen doping at the A, B, and C lattice sites. N-doping has a profound effect on Si-29 spin-lattice relaxation, and the site-dependent relaxation behavior is attributed to a difference in conduction electron properties at the different lattice sites. Si-29 T-1 measurements serve to identify the sublattice damages in SHI irradiated 6H-SiC. By determining the spin-lattice relaxation rates as a function of the SHI irradiation ion fluences, the change in relaxation behavior is correlated to the damage production mechanism. The sublattice damage leads to discernable changes in the interaction between the mobile unpaired electrons in the conduction band and the nuclear site, which profoundly influence the NMR relaxation properties. Our relaxation studies also provide evidence for site-dependent localized effects and a decrease in carrier spin density in the conduction band for the SHI irradiated 6H-SiC.

Lithium speciation in the LiPF6/PC electrolyte studied by two dimensional heteronuclear overhauser enhancement and pulse field gradient diffusometry NMR - Kumar, Vikas; Reddy, R. Ravikanth; Kumar, B. V. N. Phani; Avadhani, Chilukuri V.; Ganapathy, Subramanian; Chandrakumar, Narayanan; Sivaram, Swaminathan (Journal of Physical Chemistry C, 2019)
Electrolytic dissociation of lithium hexafluorophosphate (LiPF6) in the nonaqueous cyclic propylene carbonate (PC) has been investigated in the wide range of concentration (0.05-3.5 M) by Li-7 solution-state nuclear magnetic resonance (NMR) spectroscopy. Two-dimensional heteronuclear Overhauser enhancement spectroscopy NMR experiments have not only enabled the cation solvation and ion-pairing to be directly monitored but additionally evidence anion solvent interaction at higher concentrations (>1.2 M) of the PC electrolyte. Preliminary analysis of kinetic nOe data has been made to determine site-dependent cross-relaxation rates for the spatial interaction of the solvent with the Li+ cation and the PF6- anion. The concentration dependence of the Li-7 NMR self-diffusion coefficient (D-self), determined using very strong pulsed magnetic field gradients (similar to 1700 Gauss/cm), depicts two breaks to mark the solvation and ion-pairing events in a distinct manner. This in turn has aided the determination of solvent coordination number and average sizes of solvated and ion-paired clusters. Our results indicate that in the contact ion pair (CIP)-dominated electrolyte (>2 M), lithium-ion mobility across the solvated and ion-paired environments appears to be inhibited which makes the spectral distinction of solvated and ion-paired environments possible. The concentration dependence of the Li-7 NMR spectral and diffusometry data is in striking correspondence with that of bulk conductivity measurements and point to the detrimental effect of CIP aggregates in impeding the ionic conductivity at high salt concentrations. These results have significance in understanding the structure and dynamics of lithium-ion solvates that are ubiquitous in the working environment of a lithium-ion battery.